Reconstruction of The Restitution Concept In Handling Corruption Cases - Stenly Christian Tania; Sulbadana Sulbadana; Syachdin Syachdin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This research focuses on the reconstruction of the concept of restitution in handling corruption cases. restitution sanction is one of the sanctions that only exists in corruption crimes. this sanction has special characteristics in accordance with the spirit of eradicating corruption crimes, namely restoring state losses. the issues raised in this research are about the portrait of the construction of additional criminal sanctions for restitution payments in the Anti- Corruption law and the analysis of the reformulation of criminal sanctions for restitution payments in the Anti-Corruption law as criminal law reform. this research uses the normative legal research method of jurisprudence, with a qualitative approach to concepts, statutes and doctrines. The conclusion of the research is that the imposition of restitution payments in the eradication of corruption as stipulated in Article 18 of the Law on the Eradication of Corruption is a means that can be applied to realize recovery efforts or recovery of state finances caused by criminal acts of corruption, The payment of restitution is imposed on the perpetrator of the crime of corruption in the amount of property obtained from the crime of corruption and the amount of property that has been transferred by the perpetrator to another party where the other party is not prosecuted and does not commit an illegal act of criminal law must still be sanctioned by restitution and the sanctioning of the perpetrator of the crime of corruption must use the classification of the perpetrator in the category of the position being held. In addition, the indictment against the crime of corruption must be accompanied by the formulation of a request for restitution sanctions against the perpetrators of corruption.